Preservación de madera con taninos - González Laredo, Rubén Francisco (Instituto de Ecología, A.C., 2016)
Three ideas for the application of tannins as possible wood preservatives against wood-destroying agents are presented. A brief description of the natural defense mechanisms of trees is presented. These mechanisms are activated by stimuli and attacks. During these processes, the production of chemical compounds (phytoalexins) is activated as a defense against pathogens. Tannins or vegetal polyphenols occur in high concentrations in the defense systems of living tissues, indicating that they could be effective preservatives. There are two kinds of tannins: condensed and hydrolizable. In this review paper, the formation of metal-tannin compounds, the synthesis of phytoalexins and a phenomenon know n among w ood chemists as derivation of wood, which refers to the chemical modification of wood, are described. A few figures are included to illustrate the structures of the chemical compounds. A mong the main advantages of the commercial formulation of wood preservatives based on tannins is the reduced environmental impact of their preparation and application, leading to greater safety for users. The potential social and economical implications of these products as substitutes for oilderivatives are highlighted. However, there are still many studies to be done before these products can be successfully applied in the field.